2009
DOI: 10.1080/00288230909510505
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ewe size and nutritional regimen beginning in early pregnancy on ewe and lamb performance to weaning

Abstract: Ewe size, pregnancy nutrition and pregnancy rank are known to affect the productive performance of ewes and their offspring. The aim of the present study was to compare the effects of two nutritional regimens, from day 21 to day 140 of pregnancy, in singleton-and twin-bearing ewes of two different mean weights, taken from a single flock. The study included Large ewes offered Ad lib (Large-Ad lib, n= 151), Large ewes offered Maintenance (Large-Maintenance, n = 153), Small ewes offered Ad lib (Small-Ad lib, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 21 publications
6
53
0
4
Order By: Relevance
“…A study by Kenyon et al (2009) found that low body weight ewes had lighter lambs than high body weight ewes at 100 days of lactation. We did not find any differences in birth weight between lambs born to ewes of different BCS, although there is evidence that nutrition during pregnancy can affect birth weight of the lambs depending on the timing and duration of the under-or over-nutrition period (Kenyon et al, 2009;Redmer et al, 2004). Pregnancy lengths were shorter in HBC compared to LBC ewes, with MBC ewes having intermediate pregnancy lengths.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study by Kenyon et al (2009) found that low body weight ewes had lighter lambs than high body weight ewes at 100 days of lactation. We did not find any differences in birth weight between lambs born to ewes of different BCS, although there is evidence that nutrition during pregnancy can affect birth weight of the lambs depending on the timing and duration of the under-or over-nutrition period (Kenyon et al, 2009;Redmer et al, 2004). Pregnancy lengths were shorter in HBC compared to LBC ewes, with MBC ewes having intermediate pregnancy lengths.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, metabolic and endocrine parameters that provide measures of energy balance may be associated with the level of hunger experienced by the animal, as estimated using motivational tests. In addition, nutrition during pregnancy may have implications for the offspring; undernutrition during pregnancy may lead to lower birth (Kenyon et al, 2009;Redmer et al, 2004) and weaning weights (Kenyon et al, 2009a). Ewe nutrition also has implications for wool parameters (Adams et al, 2002(Adams et al, , 2007.…”
Section: Introductionmentioning
confidence: 98%
“…Studies have outlined the influence of both maternal BCS and gestational nutrition on lamb birth weight (Gardener et al, 2005;Kenyon et al, 2009;Caton and Hess, 2010;Meyer et al, 2010), highlighting its importance in the detection of fetal growth restriction and/or adequate maternal nutrition. In the present study, despite the difference in ewe DMI and BCS (McGovern et al, 2015), there was a lack of difference observed in lamb birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have investigated the effects of gestational nutrition on fetal development (Kenyon et al, 2009(Kenyon et al, , 2011aBlair et al, 2011), this study focused on assessing offspring performance after individual ewe feeding, where daily feed intake of the ewe, as opposed to group feeding, was monitored, thus allowing for a more accurate individual energy intake calculation on a daily basis. Although there was a lack of difference observed in lamb birth weight, organ weight, and glucose concentration, significant effects from the nutritional imbalance were observed in lamb thoracic circumference, fore leg length, and lamb behavior, measured at birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation